PENGARUH LINGKUNGAN KERJA FISIK DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT DURAQUI PT CEMERLANG LIMO DEPOK - Muhammad Shuniel Ramzie Singh; Windy Gustia Wardani (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the physical work environment and work stress on employee performance at PT Duraquipt Cemerlang Limo Depok, both partially and simultaneously. This type of associative research with a quantitative approach. The research sample was 50 respondents. Data analysis methods used in research include instrument tests consisting of validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, correlation coefficients, coefficient of determination tests, hypothesis tests consisting of partial t test and simultaneous f test. The research results show that the physical work environment has an influence on employee performance with a calculated t value > t table or (3.282 > 2.007) and a significance value of 0.000 < 0.05. Work stress has a positive and significant influence on employee performance with a calculated t value > t table or (3.443 > 2.007) and a significance value of 0.000 < 0.05. The physical work environment and work stress have a positive and significant influence on employee performance with a calculated F value > F table or (35.043 > 3.180) and a significance value of 0.000 < 0.05. The physical work environment and work stress on employee performance have an influence. The results of the R-square value show that the physical work environment and work stress together have an influence on employee performance variables of 58.2%, while the remaining 41.8% is influenced by factors. or other variables not studied.